2012
DOI: 10.3945/jn.112.160341
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Low-Protein Diet Induces Gender-Dependent Changes in Epigenetic Regulation of the Glucose-6-Phosphatase Gene in Newborn Piglet Liver

Abstract: Glucose-6-phosphatase (G6PC) plays an important role in glucose homeostasis because it catalyzes the final steps of gluconeogenesis and glycogenolysis. Maternal malnutrition during pregnancy affects G6PC activity, yet it is unknown whether epigenetic regulations of the G6PC gene are also affected. In this study, we fed primiparous, purebred Meishan sows either standard-protein (SP; 12% crude protein) or low-protein (LP; 6% crude protein) diets throughout gestation and analyzed hepatic G6PC expression in both m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 47 publications
1
82
0
1
Order By: Relevance
“…In this respect, the concept of nutritional programming appears promising. Indeed, numerous studies in (omnivorous) mammals have shown that modifying macronutrient (carbohydrates, proteins, lipids) intakes at early life stages can cause long-term modifications to metabolism, especially glucose metabolism (Ozanne et al, 1996;Patel and Srinivasan, 2002;Burdge and Lillycrop, 2010;Waterland and Jirtle, 2003;Metges et al, 2014;Jia et al, 2012). To the best of our knowledge, no such data are available for strict mammalian carnivores such as the cat Felis catus or mink Mustela vison.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In this respect, the concept of nutritional programming appears promising. Indeed, numerous studies in (omnivorous) mammals have shown that modifying macronutrient (carbohydrates, proteins, lipids) intakes at early life stages can cause long-term modifications to metabolism, especially glucose metabolism (Ozanne et al, 1996;Patel and Srinivasan, 2002;Burdge and Lillycrop, 2010;Waterland and Jirtle, 2003;Metges et al, 2014;Jia et al, 2012). To the best of our knowledge, no such data are available for strict mammalian carnivores such as the cat Felis catus or mink Mustela vison.…”
Section: Introductionmentioning
confidence: 94%
“…Rainbow trout also has a high dietary protein requirement, i.e. more than 35% of diet dry matter (NRC, 2011), probably linked to persistent amino acid catabolism for energy purposes (Kaushik and Seiliez, 2010 (Ozanne et al, 1996;Patel and Srinivasan, 2002; Burdge and Lillycrop, 2010;Waterland and Jirtle, 2003;Metges et al, 2014;Jia et al, 2012). To the best of our knowledge, no such data are available for strict mammalian carnivores such as the cat Felis catus or mink Mustela vison.…”
mentioning
confidence: 96%
“…Nutritional programming, a currently promising nutritional strategy, is based on early-life modifications induced during a 'sensitive' period by environmental stimuli (strictly nutritional or not, such as temperature, hypoxia, etc.) that result in long-term modifications in metabolism, especially glucose metabolism, later in life (Jia et al, 2012;Metges et al, 2014;Ozanne et al, 1996;Patel and Srinivasan, 2002). Several studies have demonstrated that one decisive point in this concept is that the susceptibility of organisms is limited to a critical ontogenic period, also known as a window of metabolic plasticity, during which an environmental stimulus may affect metabolism in the long-term (for review, see McMillen and Robinson, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in a model of undernutrition (eg, low protein diet) during pregnancy in piglets, the low-protein male offspring had increased hepatic G6Pase expression associated with lower trimethylated histone H3 [K9] in the proximal promoter of porcine G6Pase compared to the controls. 37 Collectively, these studies suggest that the expression of hepatic G6Pase is tightly governed by the trimethylation status of histone H3 [K9] in the short and long term. Although previous studies have demonstrated that uterine artery ligation can also lead to the long-term silencing of gene expression (eg, PDX-1) in postnatal life due to increases in histone H3 [K9] methylation, 12 this is the first study to demonstrate that the maternal hypoxia in pregnancy can also lead to hypermethylation of gene promoters in the long term.…”
Section: Mementioning
confidence: 99%